The appreciation of the illumination of the Prayer Book of Mary of Guelders until 1900 in Germany and the Netherlands - Overgaauw, Eef 1957- (2024)
The lavishly illuminated Prayer Book of Mary of Guelders (Berlin, SBB-PK, Ms. germ. qu. 42) was written in 1415 by Helmig die Lewe in the monastery of Marienborn near Arnhem. During the second half of the 19th cent. this manuscript gradually became known to historians of art in Germany and to church historians in the Netherlands. Its appreciation until c. 1900 depended on the point of view of its observers as well as on the gradual development of an art-historical vocabulary and the introduction of high-quality reproductions in scholarly publications.
Keywords: Gebetbuch der Maria von Geldern; Geschichte 1850-1900; Illuminierte Handschrift; Buchmalerei; Kunstgeschichtsschreibung; Devotio moderna; Deutschland; Niederlande